Energy Estimation on BLDC Electric Vehicle using MATLAB - Hasnira Hasnira; Didi Istardi (Institut Teknologi Sepuluh Nopember, 2014)
The need for an efficient electric drive system which has high torque and speed, low maintenance costs is getting increased. However, the motors which are commonly used, such as induction motors and DC motors, have not been able to meet the need. Therefore, a new model with efficiency System and energy consumption using simulated software